(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
A cross sectional study was conducted to observe the factors affecting the productive performance of dairy cattle from northern rural areas of Bangladesh during July and September 2013. Data of 105 cows, 85 (80.95%) from local and 20 (19.05%) cows from cross breed, were randomly selected for the study. A binary logistic regression, expressed by odds ratio with 95% confidence interval, was done to determine the association of daily milk production categorized into ? 2 and > 2 liters (L), based on median, with the significant explanatory variables of body weight, age at first calving, lactation period, vitamin use, type of floor and milking person. The result demonstrated that the probability of milk production of >2 L was 6.16, 4.5, 20.65 and 5.7 times higher from the with animal body weight of >140 kg, age at first calving of >36 m, lactation period of >8 m and vitamin use than that of body weight of 140 kg, age at first calving of ?36 m, lactation period of ? 8 m, and not vitamin used respectively. The chance of milk production of > 2 L was 0.25 and 0.22 times lower for mud floor, and owner milking than that of brick floor and gowala (professional milking person) respectively. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22646 Int. J. Agril. Res. Innov. & Tech. 4 (2): 41-45, December, 2014